Universalism in life and doctrine : and its superiority as a practical power, exhibited in a series of discourses - Brooks, Elbridge Gerry, 1816-1878. (Tufts University. Tisch Library., 2021)
Second edition.; First edition published under title: Universalism, a practical power.